Aula de mim: a linguagem corporal na educação infantil e o protagonismo da criança no ensino de dança - Saryta Garrossino Guanais (2017)
Despite many discussions, Dance at school still takes on the character of presentations for commemorative dates, and its mode of teaching is still based on copies and repetitions. In Child Education, these references are seen more frequently because they do not believe in the learning potential of the young child, so the ways of working continue to be mistaken and the small child continues to be neglected. Thus, this research has as its central theme the role of the young child in the teaching of Dance and seeks to verify the possibility of developing a teaching / learning work in the Body Language: Dance in Early Childhood Education, which besides targeting the specific contents of the area, Consider the child protagonist of this process and possibility to develop their creativity, allowing their choice by symbolic and extra everyday movements. Some of the reflections presented here are based on the researcher's experience with the EBA / UFMG Children's Body Language Project and the speech of one of the children participating in the project explaining what kind of activity she was doing: "It's me!" Thus, the application of a pedagogical / artistic methodological proposal in the UMEI Vila Estrela of the Municipal Education Network of Belo Horizonte, with children from four to five years of age, was the object of study. This proposal has as its main structural axes the structural and educational concepts of Dance (Marques, 2001), elementary movements (Laban, 1990) and the Reggio Emilia approach in order to instigate the teen of protagonism and the choice of movements of child in the creative process in Dance. The results point to the importance of a new vision about the child and the teaching / learning of the Body Language: Dance.